HAK SUARA KREDITOR SEPARATIS DALAM PROSES PENGAJUAN UPAYA PERDAMAIAN MENURUT UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Kemala Atika Hayati; Tan Kamello; Dedi Harianto; Hasim Purba (USU LAW JOURNAL, 2016)
ABSTRACT Act No. 37 Year 2004 on Bankruptcy and Suspension of Payment, do not allow the sound to be heard in a secure creditor approval peace efforts in bankruptcy unless the separatist creditors to waive his right to be but in the review of the decision of the Supreme Court No. 62 PK/Pdt.Sus/2012 considered it essential to secure creditor voice in decision making peace efforts. This leads to the need to be assessed on the direction of the voting rights in a secure creditor filing approval peace efforts under the Act No. 37 Year 2004 on Bankruptcy and Suspension of Payment. Regarding the position of creditors separatists had no voice in the decision making peace efforts in Act No. 37 Year 2004 on Bankruptcy and Suspension of Payment and the basis of the Supreme Court considers it important to pay attention to the position of creditors voting rights in decision-making separatist peace efforts. Keywords : Bankruptcy, Creditor Voting Rights Separatists, Filing Peace  Efforts.